Bioregenerative Life Support System Research as part of the DLR EDEN Initiative - Bamsey, Matthew; Schubert, Daniel; Zabel, Paul; Zeidler, Conrad; Poulet, Lucie (2014)
In 2011, the DLR Institute of Space Systems launched a research initiative called EDEN - Evolution and Design of Environmentally-closed Nutrition-Sources. The research initiative focuses on bioregenerative life support systems, especially greenhouse modules, and technologies for future crewed vehicles. The EDEN initiative comprises several projects with respect to space research, ground testing and spin-offs. In 2014, EDEN's new laboratory officially opened. This new biological cleanroom laboratory comprises several plant growth chambers incorporating a number of novel controlled environment agriculture technologies. This laboratory will be the nucleus for a variety of plant cultivation experiments within closed environments. The utilized technologies are being advanced using the pull of space technology and include such items as stacked growth systems, PAR-specific LEDs, intracanopy lighting, aeroponic nutrient delivery systems and ion-selective nutrient sensors. The driver of maximizing biomass output per unit volume and energy has much application in future bioregenerative life support systems but can also provide benefit terrestrially. The EDEN laboratory also includes several specially constructed chambers for advancing models addressing the interaction between bioregenerative and physical-chemical life support systems. The EDEN team is presently developing designs for containerized greenhouse modules. One module is planned for deployment to the German Antarctic Station, Neumayer III. The shipping container based system will provide supplementation to the overwintering crew's diet, provide psychological benefit while at the same time advancing the technology and operational readiness of harsh environment plant production systems. In addition to hardware development, the EDEN team has participated in several early phase designs such as for the ESA Greenhouse Module for Space System and for large-scale vertical farming. These studies often utilize the Institute of Space Systems Concurrent Engineering Facility.